PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPS DENGAN MENGGUNAKAN PENDEKATAN CONTEXTUAL TEACHING LEARNING (CTL) DI SD - PUJIATI, SRI (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research base of fach in field that study of IPS in Class IV SD N 01 Sasak West Pasaman,Teacher still predominate studies process and cannot entangle student participation directly. The condition result make lower result of learning study of IPS as according to KKM which have been specified that is 70. Therefore not conducted by research with aim to increase result of learning IPS by using contextual teaching learning of according to wina ( 2009 : 255 ). In Class IV SD N 01 Sasak West Pasaman. That research use Approach qualitative and is quantitative, while this Type research that is Research Action Class (PTK ) with this Device research cover, (1) Planing, (2) Execution, (3) perception / observation, ang (4) Refleksi. Result of research be grow up result of RPP, execution, and result learn student. Become can be concluded that study of IPS by using contextual teaching learning (CTL) can improve result learn IV SD N class student 01 Sasak west Pasaman. Kata kunci : Hasil Belajar; Pembelajaran IPS; Pendekatan Contextual Teaching Learning (CTL )